A study of extraction and characterization of alginates obtained from brown macroalgae Sargassum duplicatum and Sargassum crassifolium from Indonesia - Decky J. Indrani; Emil Budianto (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Worldwide commercially available alginate have been used for tissue engineering purposes. The macroalgae Sargassum obtained from Indonesia have been used for various purposes, however, they have not been applied for tissue engineering scaffolds. Purpose: This study was aimed to extract alginate from the macroalgae Sargassum from Indonesia sea and to characterize in morphology, chemical element and functional groups. Methods: Macroalgae Sargassum duplicatum (S. Duplicatum) and Sargassum crassifolium (S. Crassifolium) were collected from Banten, Indonesia. Extraction of alginates were carried out using the alkaline extraction procedure. Scanning electron microscopy as well as X-ray Fluorescence and Fouirer Transform Infra-Red spectroscopy were used to characterize the extracted powders. Obtained data from the extracted powders were compared to those of the commercially available alginate. Results: Extraction using the alkaline method has resulted in S.duplicatum and S.crassifolium alginate powders. Alginate particles were suggested as irregular shapes with various dimension. Element components were mainly Na and Ca, whereas, minor elements were considered as negative impurities. COO- and C-O-C groups were evident in the finger print regio. The characteristics of Alginates extracted from the macroalgae S.duplicatum and S.crassifolium found similar to those of the commercially available alginate. Conclusion: Extraction obtained from the macroalgae S.duplicatum and S.crassifolium showed the typical alginate and the morphology, chemical element and functional groups were in agreement with those of the commercially available alginate.Latar belakang: Alginat dari berbagai penjuru dunia telah digunakan untuk kegunaan rekayasa jaringan. Alginat dari alga makro Sargassum yang diperoleh dari Indonesia telah digunakan untuk berbagai kegunaan, namun ini belum diterapkan untuk scaffold jaringan. Tujuan: Untuk mengekstrak alginat dari alga makro Sargassum perairan Indonesia dan untuk memperoleh karakteristik alginat dalam morfologi, unsur kimia dan gugus fungsi. Metode: Alga makro Sargassum dari spesies Sargassum duplicatum (S. Duplicatum) dan Sargassum crassifolium (S. Crassifolium) diperoleh dari Banten, Indonesia. Ekstraksi alginat dilakukan dengan menggunakan prosedur ekstraksi alkali. Scanning electrone microscope, X-ray fluorescence dan Fouirer transform infra-red spektroscope digunakan untuk mengarakterisasi bubuk alginat hasil ekstraksi. Data yang diperoleh dari serbuk laginat dibandingkan dengan yang tersedia secara komersial. Hasil: Ekstraksi menggunakan metode alkali telah menghasilkan serbuk alginat dari S.duplicatum dan S. crassifolium. Morfologi partikel alginat terlihat tidak teratur dengan berbagai dimensi. Elemen Na dan Ca muncul sebagai komponen utama, sedangkan, elemen minor dianggap sebagai pengotor. Gugus fungsi COO-dan COC terdeteksi di regio sidik jari. Karakteristik alginat S.duplicatum dan S.crassifolium ditemukan sesuai dengan karakteristik alginat yang tersedia secara komersial. Simpulan: Serbuk yang diperoleh dari alga makroi S. duplicatum dan S.crassifolium menunjukkan kekhasan alginat dan morfologi, unsur kimia dan kelompok fungsional alginat sesuai dengan yang tersedia secara komersial.